2000
DOI: 10.1007/bf02725342
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative plasma plasminogen activator inhibitor type-1 and serum C-reactive protein levels in patients with colorectal cancer

Abstract: This study did not show a strong correlation between plasma PAI-1 and serum CRP in patients with colorectal cancer. Serum CRP was found to be a Dukes independent prognostic variable in this patient cohort, and was found to identify a subgroup of curatively resected patients at risk for short survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
86
1
2

Year Published

2003
2003
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(100 citation statements)
references
References 36 publications
11
86
1
2
Order By: Relevance
“…It On univariate and multivariate analysis, deprivation, Dukes stage and the systemic inflammatory response were significant independent predictors of overall survival. These results are therefore consistent with previous studies showing an association between deprivation and overall survival (Kogevinas and Porta, 1997;Hole and McArdle, 2002), and the presence of a systemic inflammatory response and overall survival (Nozoe et al, 1998;Nielsen et al, 2000) in patients undergoing apparently curative surgery for colorectal cancer.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It On univariate and multivariate analysis, deprivation, Dukes stage and the systemic inflammatory response were significant independent predictors of overall survival. These results are therefore consistent with previous studies showing an association between deprivation and overall survival (Kogevinas and Porta, 1997;Hole and McArdle, 2002), and the presence of a systemic inflammatory response and overall survival (Nozoe et al, 1998;Nielsen et al, 2000) in patients undergoing apparently curative surgery for colorectal cancer.…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, there is evidence that the systemic inflammatory response (as evidenced by C-reactive protein) predicts recurrence (McMillan et al, 1995), overall (Nielsen et al, 2000;McMillan et al, 2003) and cancer-specific (McMillan et al, 2003) survival, independent of stage, in patients who have undergone curative resection for colorectal cancer.…”
mentioning
confidence: 99%
“…Several studies have shown that elevated circulating C-reactive protein concentrations are associated with poor survival in patients with colorectal cancer (McMillan et al, 1995;Nozoe et al, 1998;Nielsen et al, 2000;Wigmore et al, 2001;McMillan et al, 2003;Chung and Chang, 2003). However, the relationship between C- Figure 1 The relationship between the cumulative prognostic score (0 .…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence that the presence of a systemic inflammatory response, as evidenced by elevated circulating concentrations of C-reactive protein, is associated with increased recurrence and poor survival in patients undergoing potentially curative surgery for colorectal cancer (McMillan et al, 1995Nozoe et al, 1998;Nielsen et al, 2000;Wigmore et al, 2001;Chung and Chang, 2003). However, some of these studies have questioned whether C-reactive protein has prognostic value independent of conventional pathological criteria including Dukes' stage (Wigmore et al, 2001;Chung and Chang, 2003).…”
mentioning
confidence: 99%
“…It has been demonstrated that the presence of a systemic inflammatory response, as evidenced by elevated circulating concentrations of C-reactive protein, is associated with increased recurrence and poor survival, independent of Dukes stage, in patients undergoing potentially curative surgery for colorectal cancer (McMillan et al, 1995(McMillan et al, , 2003Nielsen et al, 2000). However, in these studies, few patients had received adjuvant chemotherapy.…”
mentioning
confidence: 99%